Credit Risk Mitigation through CDSs: Evidence from the French Credit Derivative Market - Navick, Laura (2014)
This thesis provides four methodologies for estimating risk-neutral default probabilities. First, by using the Hull-White (2000) approach relying on bond prices. Secondly, by bootstrapping hazard rates from CDS spreads through the JP Morgan (1999) model, whilst assuming a piecewise constant hazard rate function. Thirdly, by applying Hull and White’s (2003) framework, while supposing a piecewise constant credit event probability density function. Finally, the hypothesis of a piecewise linear default probability distribution is examined instead. Additionally, this study will apply the Hull-White (2000) spread formula for the valuation process of CDSs and will thus offer an additional application to a theoretical framework that suffers from a lack of tangible data examples. This is operated in the case of the payoff being contingent on default by one reference entity only and an absence of counterparty default risk. All aforementioned models are tested with real market data on five firms belonging to the French stock market (the CAC40). Theoretical CDS spreads are calculated for various maturities (from 1-10 years), 4th July 2014 being the study’s starting point. Results are satisfactory: theoretical and market CDS spreads share comparable levels; yet, Hull and White’s framework tends to overestimate CDS spreads when compared with quoted ones in the short term. However, an inherent limit to the model remains: the latter is built on rather stringent assumptions, making it unable to adjust to some real-life situations where parameters deviate from these suppositions.